Augmented Reality and Coding in Education: A Food Pyramid Media to Foster Self-Directed Learning and Computational Thinking - Ardiyanti, Ni Putu Mita; Jayanta, I Nyoman Laba (Mimbar Ilmu, 2024)
The issue of low self-directed learning and Computational Thinking skills among elementary school students remains a challenge in the learning process. This study aims to develop an augmented reality (AR)-based food pyramid media integrated with coding to enhance self-directed learning and Computational Thinking skills of fifth-grade elementary school students. The research employed the ADDIE development model. The media's validity was assessed by experts, while its practicality and effectiveness were evaluated through classroom implementation. Data were collected using self-directed learning questionnaires, essay questions to measure Computational Thinking skills, and interviews with homeroom teachers to strengthen qualitative data. The findings revealed that the AR-based food pyramid media has a high validity level, with expert evaluations categorized as highly valid. The media also demonstrated high practicality, receiving positive responses from both students and teachers during classroom implementation. The effectiveness test showed that the media significantly improved students' self-directed learning and Computational Thinking skills. The statistical test results indicated a significance value (sig. 2-tailed) of < 0.001 for both variables. This result shows that Fcalculated > Ftable, rejecting H₀ and accepting H₁, indicating a significant impact of the media on enhancing students' self-directed learning and Computational Thinking skills. In conclusion, the augmented reality and coding-based food pyramid media can serve as an effective learning tool to improve students' self-directed learning and Computational Thinking skills.